2019
DOI: 10.26508/lsa.201900549
|View full text |Cite
|
Sign up to set email alerts
|

Initial phospholipid-dependent Irgb6 targeting toToxoplasma gondiivacuoles mediates host defense

Abstract: Irgb6 has a role in the cell-autonomous response against T. gondii and involves ubiquitination and breakdown of vacuoles via binding of a specific phospholipid on the parasitophorous vacuole membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 77 publications
8
60
2
Order By: Relevance
“…However, p62-PV association was not inhibited by ROP5A but instead phenocopied the PV-association patterns of Irgb6 ( Fig 4D and 4E ). Irgb6 has recently been shown to be required for p62-PV association in IFNγ-stimulated cells, which is consistent with these observations [ 89 ]. The ROP18 [ 4 ] and ROP17 kinases [ 6 ] phosphorylate and inactivate Irga6 and Irgb6.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, p62-PV association was not inhibited by ROP5A but instead phenocopied the PV-association patterns of Irgb6 ( Fig 4D and 4E ). Irgb6 has recently been shown to be required for p62-PV association in IFNγ-stimulated cells, which is consistent with these observations [ 89 ]. The ROP18 [ 4 ] and ROP17 kinases [ 6 ] phosphorylate and inactivate Irga6 and Irgb6.…”
Section: Resultssupporting
confidence: 81%
“…The ROP5 locus consists of ROP5A , ROP5B and ROP5C genes, which differ in copy number between strains, and is under diversifying selection [ 3 , 9 , 12 , 13 , 81 , 85 ]. ROP5B and ROP5C isoforms of virulent strains bind to and prevent accumulation of effector IRGs on the parasite’s PVM, including Irga6 and Irgb6 [ 3 , 4 , 81 ], which are required for host resistance to primary infection [ 88 , 89 ]. In contrast, ROP5A lacks a defined host binding partner and function, but does promote virulence by an unknown mechanism that is sensitive to copy number.…”
Section: Resultsmentioning
confidence: 99%
“…Because the two GRAs were not identified as components of the ROP5/18 complex from previous proteomic studies 27 , 28 , it is unlikely they directly bind to the IRGB6 on the PVM and inhibit its polymerization. A recent study suggested that IRGB6 recruitment is dependent on the recognition of specific phospholipids present on the PVM 88 . It is therefore also possible that the increased IRGB6 loading on the vacuole of Δ TGGT1_263560 or Δ TGGT1_269950 parasites is due to a change of PVM lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection of murine cells with the avirulent ME49 and Prugniaud strains, the cytosolically abundant Irga6, Irgb10 and Irgb6 proteins (Martens et al, 2004; Martens & Howard, 2006) diffuse to the vacuolar membrane (Khaminets et al, 2010; Lee et al, 2020). IRGs loading at the PVM exhibits spatial hierarchy and cooperation (Hunn et al, 2008; Khaminets et al, 2010).…”
Section: Discussionmentioning
confidence: 99%